Unresolved Sovereignty and the Anthropocene Novel: Alexis Wright's The Swan Book*. Issue 4 (2nd October 2018) - Mead, Philip
ABSTRACT: The recent "Uluru Statement from the Heart" (May, 2017), and the Final Report of the Referendum Council (June, 2017) are significant expressions of a rapidly evolving discourse on sovereignty in Australia. Alexis Wright's The Swan Book (2013) is a futuristic meditation on the limits of sovereignty from an Indigenous perspective: what if national borders disappear under the rising waters of global warming? What if national governments are superseded by global rule? The Swan Book explores these scenarios in a complex interplay of utopian and dystopian modes. This article argues that Alexis Wright's work is an instance of how the Indigenous world novel can address real world issues of anthropocene futures, Indigenous rights and national sovereignty.